Comprehensive elucidation of the multifunctional role of lithium nitrate in lithium–sulfur batteries: Expanding beyond shuttle suppression - Lee, Yun-Jeong; Lee, Yurim; Kim, So Hee; Bae, Jong-Seong; Kim, Ki-Hyun; Lee, Do-Joong; Lee, Chang Hoon; Yu, Seung-Ho (Wiley, 2025)
Lithium–sulfur (Li–S) batteries are promising candidates for next-generation energy storage systems, but practical use is limited by polysulfide (PS) shuttling and Li metal anode instability. Lithium nitrate (LiNO3) is widely used to mitigate these issues; however, its interfacial effects across the anode, electrolyte, and cathode during operation are not fully understood. Here, operando optical microscopy with a custom side-by-side cell enables simultaneous monitoring of the Li anode, liquid electrolyte, and sulfur cathode in a single field of view under conditions with and without LiNO3. In the absence of LiNO3, the Li surface undergoes rough stripping and fragmented, non-coalescent deposition, accompanied by PS-induced corrosion and accumulation of parasitic byproducts at the anode-electrolyte interface. Redness Intensity (RI), introduced to quantify electrolyte-phase PS dynamics, indicates sustained transport toward the anode and delayed conversion to elemental sulfur. By contrast, LiNO3 induces uniform Li stripping and the growth of aggregated, interconnected deposits, while mitigating PS crossover and promoting efficient sulfur crystallization at the cathode. Complementary SEM-EDS, UV–vis, XPS, TXM, and CT analyses corroborate these observations. By elucidating the multifunctional role of LiNO3, this study clarifies the interfacial dynamics that govern Li–S battery performance.